LEADERSHIP DYNAMICS IN FACING THE CHALLENGES OF GLOBALIZATION IN ISLAMIC HIGHER EDUCATION - Firda Prasetyowati; Ali Nasith (Benchmarking: Jurnal Manajemen Pendidikan Islam, 2025)
The dynamics of Islamic Religious Colleges (PTKI) in Indonesia are greatly influenced by globalization. PTKI are required to improve academic quality, increase global competitiveness, and adopt information technology, all of which are done without ignoring Islamic principles as a basis. The purpose of this study is to analyze various PTKI leadership strategies in facing the challenges of globalization. In this article, it was found that transformational leadership and servant leadership are two relevant strategies. Transformational leadership encourages innovation and motivation, while servant leadership emphasizes individual development and service. Both of these strategies are considered to have the ability to create an inclusive, character-based academic environment that is ready to make changes throughout the world. So, to remain relevant and superior in the global education arena, PTKI requires visionary, effective, and Islamic value-based leadership.